Analysis Of Critical Thinking Dimensions In The Picture Story Atane Buja (Farming Salt) - Hardiansyah, Framz; Qomariyah, Aisyatul; Armiyati, Adinda; Rosalia, Amanda; Mustaf, Rifqy Qalib (Global Action and Education for Society, 2026)
This article examines children's illustrated stories as a literary work that has the potential to instill character values in the midst of the condition of children who experience obstacles in processing information properly, building relationships between various information, analyzing information, evaluating, and concluding it. The character value in question is the value of the Pancasila student profile, especially in the critical reasoning dimension. This study aims to determine the value of the critical reasoning dimension contained in the illustrated story of a Madurese child